“Maybe a Long Fast Is Good for You”: Health Conceptualisations in YouTube Diet Videos - Chiu, Mu-Chi; Penders, Bart (Frontiers in Communication, 2021)
In this paper, we study which health conceptualisations are promoted or supported by intermittent fasting, no-carb-no-sugar, and endomorph Diet YouTubers and how they relate to existing definitions of health. In order to openly understand how YouTubers present health concepts, we will study health conceptualisations in YouTube diet videos qualitatively, through the use of thematic analysis. We identify five main themes: weight management, prior dietary awareness, diet literacy, quality of life, and the satisfaction of functional needs. We find that YouTubers substitute the WHO’s pursuit of a complete state of well-being by an implicit, tacit version of new health concepts. The tacit form allows them to stay practical and to focus on real-world dietary concerns, such as answers to the simple question “what should I eat to stay healthy?”. Diet YouTubers do not, however, neatly position themselves within existing health conceptualisations and they offer views on health that move beyond ‘formal’ conceptualisations, including self-inspection, timing, preparation and planning and context-design. Differing from the universal definitions of health, the Diet YouTubers we studied target specific audiences with their presentations of healthy eating.